Preparation and Evaluation of Buccal Bioadhesive Tablets Containing Clotrimazole - Singh, S.; Jain, S.; Muthu, M. S.; Tilak, R. (Current Drug Delivery, 2008)
Buccal bioadhesive tablets of clotrimazole (CTZ) and clotrimazole: hydroxypropyl-β-cyclodextrin (CTZ-HPβCD) complex were prepared by using polymer xanthan gum in combination with carbopol 974P. The prepared buccal bioadhesive tablet formulations were evaluated for physicochemical characteristics (weight, hardness, friability, diameter, and drug content), swelling index, microenvironment pH, in-vitro drug release, bioadhesion strength, residence time and duration of antifungal activity (in-vitro). The dissolution of CTZ from the prepared tablets into phosphate buffer (pH 6.8) was controlled up to 8 h. All the prepared tablets gave reasonable in-vitro residence time (7.13 - 9.34 h). X-ray diffraction (XRD) studies of the CTZ-HPβCD complex, made by kneading and freeze-dried method, showed no CTZ crystal signals, demonstrating the inclusion of CTZ in the hydrophobic cavity of hydroxypropyl-β-cyclodextrin (HPβCD) and formation of amorphous inclusion complex. Duration of the antifungal activity was measured by the inhibition zone of Candida albicans by agar diffusion assay. It is evident from the results obtained, the prepared buccal bioadhesive tablets of CTZ would markedly prolong the duration of the antifungal activity and may prove to be a viable alternative to the conventional local oral medication.
Keywords: xanthan gum